My English companion: a self paced learning portal / Alice Shanthi and Lim Teck Heng - Shanthi, Alice; Lim, Teck Heng (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Language proficiency can significantly impact the learning process as it can either facilitate or hinder comprehension and mastery of subjectmatter. For non-native speakers of a particular language, improving language proficiency is crucial to ensure that they can fully understand and engage with the subject matter and communicate their ideas effectively. One way to improve language proficiency is by using online language learning resources. Using learning websites to teach English proficiency can be a great way to improve language skills. Learning websites are essential tools that can benefit learners at different skill levels and allow them to learn at their own pace (Yazon & Callo, 2021). An advantage of using educational websites is it frequently provides interactive activities and multimedia resources that make learning exciting and enjoyable (Shanthi et al., 2021).